2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6609852
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between red, green and blue light reflection photoplethysmography for heart rate monitoring during motion

Abstract: Abstract-Reflection photoplethysmography (PPG) using 530 nm (green) wavelength light has the potential to be a superior method for monitoring heart rate (HR) during normal daily life due to its relative freedom from artifacts. However, little is known about the accuracy of pulse rate (PR) measured by 530 nm light PPG during motion. Therefore, we compared the HR measured by electrocadiography (ECG) as a reference with PR measured by 530, 645 (red), and 470 nm (blue) wavelength light PPG during baseline and whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 13 publications
(33 reference statements)
2
57
1
Order By: Relevance
“…Therefore, red and near IR light are typically utilized as light sources in PPG sensors (for a review, see [18]). Recently, green-wavelength PPG devices are becoming increasingly popular for their large intensity variations in modulation that are observed during the cardiac cycle [19]–[21]. Compared to red/IR light, green LED has much greater absorptivity for both oxyhemoglobin and deoxyhaemoglobin [22], thus resulting in a better signal-to-noise ratio (SNR).…”
Section: Photoplethysmographymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, red and near IR light are typically utilized as light sources in PPG sensors (for a review, see [18]). Recently, green-wavelength PPG devices are becoming increasingly popular for their large intensity variations in modulation that are observed during the cardiac cycle [19]–[21]. Compared to red/IR light, green LED has much greater absorptivity for both oxyhemoglobin and deoxyhaemoglobin [22], thus resulting in a better signal-to-noise ratio (SNR).…”
Section: Photoplethysmographymentioning
confidence: 99%
“…Compared to red/IR light, green LED has much greater absorptivity for both oxyhemoglobin and deoxyhaemoglobin [22], thus resulting in a better signal-to-noise ratio (SNR). Several studies have compared the performance of IR and green light PPG and found that the green light achieved higher accuracy of pulse rate detection than did the IR light [20], [21]. …”
Section: Photoplethysmographymentioning
confidence: 99%
See 1 more Smart Citation
“…This PPG system was designed using APDS-9007 low powered light photo sensor that received reflectance light sourced from green light at user's finger. Green led produced 530 nm wavelength turn to be most suitable wavelength to react with blood melanin inside microvascular bed of tissue which provides better waveform [7].…”
Section: A System Designmentioning
confidence: 99%
“…Blood volume inside the microvascular bed tissue changes according to the time heart pump blood to the whole body which also known as a heart beat. This process makes PPG signal connected to any changes in human cardiovascular system [6,7].…”
Section: Introductionmentioning
confidence: 99%